Vitamin D levels of anaesthetists in the department of anaesthesiology at the University of the Witwatersrand - Kelly, Eugene Hamerton (My University, 2016)
Background and Objective There has been a recent resurgence of interest in vitamin D and its far-reaching effects in physiology and pathophysiology. Theatre personnel, and all indoor workers, should be cognisant of vitamin D deficiency as a real occupational hazard. Vitamin D deficiency is a global problem that has been studied extensively in colder climates and even been found in warmer climates. No research was identified among medical personnel in South Africa. The primary objective of this study was to describe serum 25-hydroxyvitamin D (25(OH)D) levels of anaesthetists. The secondary objective was to describe and compare factors influencing vitamin D levels in anaesthetists who are vitamin D insufficient to those who are not. These factors included: ethnicity, gender, body mass index (BMI), multivitamin use, calcium or vitamin D supplementation, sun exposure, vitamin D intake from diet alone, vitamin D intake from diet and supplementation and calcium intake (dairy). Methods Data was collected over a period of one month, in winter (mid-July to mid-August 2013). On the morning of sample collection anaesthetists agreeing to participate signed the informed consent (Appendix 2), prior to enrolment in the study. The anaesthetists then completed the questionnaire (Appendix 5). The following data was obtained from the questionnaire: age, gender, ethnic group, dietary supplementation, sun exposure, sunscreen use, BMI and diet. Each participant had 5 ml of blood collected in a standardised manner into a purple top ethylenediaminetetraacetic acid blood specimen tube. The processing of samples was done by qualified laboratory personnel using standard chemical pathology equipment and procedures. High Performance Liquid Chromatography was performed to determine 25(OH)D levels using a Shimadzu® Nexera X2 Ultra performance liquid chromatography system with a photodiode array detector (Shimadzu®, Japan). Results The median 25(OH)D was 43.8 nmol/l (IQR 26-76), with 51 of 89 (57.30 %) anaesthetists being vitamin D insufficient. There was a statistically significant association between ethnicity and vitamin D status (p<0.001). Twenty-one (80.77 %) Indian anaesthetists and 14 (70.00 %) black anaesthetists were vitamin D insufficient, as compared to only 10 (28.57%) white anaesthetists. There was no significant association between the other secondary objectives-gender (p=0.60), sun exposure (p = 0.93), vitamin D intake from diet alone (p= 0.07), vitamin D intake from diet and supplementation (p=0.05) and calcium intake (p=0.55) and vitamin D status. There was no significant difference between BMI and vitamin D status. When a comparison was made between the two groups of BMI <25 and BMI ≥25, using a Mann-Whitney test the two-tailed P value was 0.6791. There was a significant association between multivitamin use (p=0.01) and vitamin D status. Conclusion Vitamin D should no longer be a forgotten vitamin. The insufficient vitamin D levels of anaesthetist in this study, puts them at risk for pathology far beyond bone health. Adequate vitamin D levels should be seen as essential, rather than optional, even in “sunny” climates.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology
Keywords: Vitamin D; Anesthetists; 25-Hydroxyvitamin D 2